SEKO ALAS MLEBU GELAS: Pelatihan Bagi Petani Kopi di Tegalsari Purwosari Perbukitan Menoreh - Moh Soehadha (UIN Sunan Kalijaga, 2023)
Coffee is a potential commodity in Tegalsari, Menoreh Hills, Kulonprogo. Despite the potential for development, proper